Implementing Maqāṣid Syarīʿah on Social Innovation For Sustainable Zakat Management Organization in Indonesia - Piliyanti, Indah (Universitas Islam Negeri Madura, 2023)
The growth of zakat collection by zakat management organizations has increased significantly in the last two decades in Indonesia. Unfortunately, not all zakat management organizations can adapt and sustain in the long term. Social innovation encourages organizations to maintain and realize the maqāṣid of zakat management. The paper analyzes the implementation of the maqāṣid syarīʿah concept developed by Auda (2015) on the process of social innovation in zakat management organizations in Indonesia. The analysis results show that one of the creations of social innovation in the Zakat management organization in Indonesia is a community-based economic empowerment program. Zona Madina is one of the prototypes created by Dompet Dhuafa, which tried to empower community development from Zakat, sadaqah, and waqf. By using an analysis of maqāṣid, social innovation made by Dompet Dhuafa is consistent with maqāṣid al-khāṣṣah where the form of economic empowerment in zona Madina, a means of maintaining maqāṣid al-‘āmmah from Zakat. With the establishment of the zona Madina, Dompet Dhuafa realizes two things at once: moving the wheels of the community’s economy and the sustainability of the zakat management organization. This article contributes to developing strategies for Islamic philanthropic organizations in Indonesia to be sustainable by creating social-based innovation.